The study on tooth failure and fixation strength of cone bits under high temperature. (March 2020) - Yang, Yingxin; Huang, Kuilin; Song, Dongdong; Chen, Xin; Chen, Hanyu; Chen, Lian
Highlights: A device is designed to study axial/lateral loads on bit teeth at high temperature. The effects of loads at high temperature are used to evaluate fixation strength. Tooth diameter, interference magnitude, and lateral load contribute to failure. The method supports failure analysis of teeth lost from bits at high temperatures. Abstract: A high temperature drilling cone bit is more likely to experience tooth shedding because of the high bottom-hole temperature. This study analyzes such tooth loss. An experimental study and a numerical simulation are conducted of the tooth fixation strength in high temperature environments. The effects of temperature, amount of interference, tooth diameter, and lateral force on the tooth setting strength are studied. The experimental results show that the maximum fastening force is 1149.29 kg and occurs when the tooth diameter is 16 mm at 180 °C and 0.095 mm interference. The strength decreases with an increase in temperature at all three values of interference with a tooth with a 16 mm diameter. At the same temperature, the maximum fastening force is the highest and the deformation of the tooth hole is the least at 0.095 mm interference. Choosing a tooth diameter of 16 mm and 0.095 mm interference is more likely to guarantee the strength of the teeth. The results of the numerical simulation show that the maximum fastening force is highest with a 16 mm tooth diameter and 0.095 mm interference; these values also give the smallest tooth hole deformation at different temperatures. The error between the simulation results and the experimental results is less than 10%; the experimental results verify the correctness of the simulation model.